FAKTOR PENYEBAB KEKECEWAAN DAN ALASAN KONSUMEN TETAP MEMPERTAHANKAN KEKECEWAAN TERHADAP PEMBELIAN REPTIL DI TOKO TURTLE WORLD SURABAYA - Kenny Tito Wisaksono (Perpustakaan Universitas Surabaya, 2017)
ABSTRACT - This study aims to know factor caused dissatisfaction and the reason consumer enduring dissatisfaction on buying reptle at Turtle World shop in Surabaya. This descriptive research using SPSS 16 program. Sampling techniques used in this research are non probability sampling with the type of purposive sampling. Data collected directly from respondents who meet the specified characteristics of the population by distributing 120 questionaires. The samples used in this study was 200 respondents.Data proceed using Mean, Standard Deviation, and Cross Tabulation. Research result shows that Turtle World consumer who stayed in Surabaya has a positive reaction of the factor caused dissatisfaction and the reason why consumer enduring dissatisfaction on Turtle World shop. The highest mean is Time Factor and the lowest mean is Consumer Expectation. . Keywords: Consumer Behavior, Consumer, Dissatisfaction, Consumer Expectation.